(S)-10-Hydroxycamptothecin Inhibits EMT-evoked Osteosarcoma Cell Growth and Metastasis by Activating the HIPPO Signaling Pathway - Ma, Xiaoping; Chang, Junli; Sun, Xingyuan; Zhou, Chujie; Zhao, Peng; Yang, Yanping (Combinatorial Chemistry & High Throughput Screening, 2024)
Background: Osteosarcoma is the most common primary bone cancer in children and adolescents with high metastatic ability. Aim: This study aimed to explore the inhibitory effects of (S)-10-hydroxycamptothecin (HCPT) on osteosarcoma cell growth and metastasis as well as the underlying mechanism. Methods: The osteosarcoma cells of 143B and U-2 OS (U-2), treated with HCPT (20, 100, or 300 nM), underwent detections, such as CCK-8, flow cytometry, Transwell, wound healing, and immunoblotting. EMT-related key proteins, like N-cadherin, Snail, and Vimentin, were found to be down-regulated, while E-cadherin was up-regulated dose-dependently in HCPT-exposed 143B and U-2 cells. Additionally, incubation of 143B and U-2 cells with HCPT for 3 hours dosedependently reduced the expression ratios of p-LATS1/LATS1, p-MST1/MST1, p-YAP/YAP, and p-TAZ/TAZ. Results: Taken together, our study has demonstrated HCPT to inhibit osteosarcoma growth and metastasis potentially by activating the HIPPO signaling pathway and reversing EMT. Conclusion: HCPT might be a candidate agent for the prevention and treatment of osteosarcoma.
Keywords: metastasis